Comprehensive tissue specific analysis of antioxidant potential and metabolite profiling of a vulnerable therapeutic herb Ceropegia sahyadrica - Pandey, Meena; Dholakia, Bhushan B.; Saraf, Purva S.; Punekar, Sachin A.; Giri, Ashok P. (3 Biotech, 2025)
This study investigated tissue-culture of an endangered medicinal herb, Ceropegia sahyadrica, along with tissue-specific variation in antioxidant activity and GC-MS based phytochemical profiling using wild and in vitro explants. In vitro leaf explants exhibited callus induction rate of 100% in Murashige and Skoog media containing 6-benzylaminopurine (4 mu M) and 2,4-dichlorophenoxyacetic acid (2 mu M) with 5% sucrose, whereas in vitro root explant achieved 66.7% with the combination of 2 mu M 6-benzylaminopurine and 1 mu M 2,4-dichlorophenoxyacetic acid in Murashige and Skoog medium. Microtuberization was most pronounced in in vitro root explants with a maximum response of 73.3% in 1 mu M indole-3-acetic acid, 2 mu M 6-benzylaminopurine and 5% sucrose. Scanning electron microscopy imaging revealed distinct cellular organization among tissues. Further, antioxidant potential assessed through 1,1-diphenyl-2-picrylhydrazyl radical scavenging assays and estimated total phenolic content showed metabolic variation and commonality between in vitro and wild tissues. Additionally, phytochemical profiling by gas chromatography-mass spectrometry identified 201 compounds, including alkaloids, fatty acid methyl esters, flavonoids, phytosterols and other bioactive molecules with alterations in metabolite profiles between in vitro and wild tissues. These findings demonstrated that explant origin and culture condition might significantly influence metabolic responses for conservation and ensures a reliable source of bioactive compound.
Keywords: Ceropegia- Conservation; Endemic medicinal herb; GC-MS; Metabolite profiling; Tuberization